2016
DOI: 10.1063/1.4954197
|View full text |Cite
|
Sign up to set email alerts
|

Modelling of electrokinetic phenomena for capture of PEGylated ribonuclease A in a microdevice with insulating structures

Abstract: Synthesis of PEGylated proteins results in a mixture of protein-polyethylene glycol (PEG) conjugates and the unreacted native protein. From a ribonuclease A (RNase A) PEGylation reaction, mono-PEGylated RNase A (mono-PEG RNase A) has proven therapeutic effects against cancer, reason for which there is an interest in isolating it from the rest of the reaction products. Experimental trapping of PEGylated RNase A inside an electrokinetically driven microfluidic device has been previously demonstrated. Now, from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 41 publications
0
23
0
Order By: Relevance
“…This field is distorted by the presence of a set of insulating structures fabricated within the microchannel, rendering significant spatial non‐uniformities in its distribution . Insulator‐based DEP devices offer many attractive traits (e.g., low cost, low fabrication complexity, and material transparency) and therefore have been used to manipulate many types of bioparticles . Nonetheless, due to the electric charges present in the channel and particles surfaces, and to ions in solution, electrophoresis (EP) and electroosmosis (EO) compete with DEP in controlling particle motion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This field is distorted by the presence of a set of insulating structures fabricated within the microchannel, rendering significant spatial non‐uniformities in its distribution . Insulator‐based DEP devices offer many attractive traits (e.g., low cost, low fabrication complexity, and material transparency) and therefore have been used to manipulate many types of bioparticles . Nonetheless, due to the electric charges present in the channel and particles surfaces, and to ions in solution, electrophoresis (EP) and electroosmosis (EO) compete with DEP in controlling particle motion .…”
Section: Introductionmentioning
confidence: 99%
“…They concluded that observed fluid circulations were due to Joule heating induced flow inhomogeneities in the constriction region of the channel interacting with the electric field. Since then, many reports have become available in the literature where computational models predict electrothermal effects and are validated through flow field experimental observations . These studies made the dependence of Joule heating on the electric field spatial distribution (and therefore on channel geometry) evident.…”
Section: Introductionmentioning
confidence: 99%
“…The Swami and Chou groups have studied protein particle enrichment in high-conductivity media employing devices with nanoscale gaps and reported both positive and negative DEPs [ 28 , 45 47 ]. Other studies have employed triangular insulating posts with nanoscale gaps [ 48 ], cylindrical insulating structures to enrich BSA particles [ 49 ], or diamond-shaped posts to separate PEGylated ribonuclease A from non-PEGylated molecules [ 50 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the presence of insulating structures may cause appreciable thermal effects because of the enhanced resistive heating of the suspending fluid as a result of the locally amplified electric field [27–29]. This phenomenon becomes significant if highly conductive solutions are used [30]. The induced temperature gradients draw nonuniformities to the fluid properties (in particular electric conductivity, permittivity, and viscosity), which interact with the electric field yielding a volumetric body force upon the fluid [31].…”
Section: Introductionmentioning
confidence: 99%